Analysis of the Expression and Function of Key Genes in Pepper Under Low-Temperature Stress - Tang, Bingqian; Xie, Lingling; Yang, Huiping; Li, Xiumin; Chen, Ying; Zou, Xuexiao; Liu, Feng; Dai, Xiongze (Frontiers in Plant Science, 2022)
The mechanism of resistance of plants to cold temperatures is very complicated, and the molecular mechanism and related gene network in pepper are largely unknown. Here, during cold treatment, we used cluster analysis (k-means) to classify all expressed genes into 15 clusters, 3,680 and 2,405 differentially expressed genes (DEGs) were observed in the leaf and root, respectively. The DEGs associated with certain important basic metabolic processes, oxidoreductase activity, and overall membrane composition were most significantly enriched. In addition, based on the homologous sequence alignment of Arabidopsis genes, we identified 14 positive and negative regulators of the ICE-CBF-COR module in pepper, including CBF and ICE, and compared their levels in different data sets. The correlation matrix constructed based on the expression patterns of whole pepper genes in leaves and roots after exposure to cold stress showed the correlation between 14 ICE-CBF-COR signaling module genes, and provided insight into the relationship between these genes in pepper. These findings not only provide valuable resources for research on cold tolerance, but also lay the foundation for the genetic modification of cold stress regulators, which would help us achieve improved crop tolerance. To our knowledge, this is the first study to demonstrate the relationship between positive and negative regulators related to the ICE-CBF-COR module, which is of great significance to the study of low-temperature adaptive mechanisms in plants.